Data Storage System Arrival and Departure Airnav Halim Perdana Kusuma Airport - Ritzkal Ritzkal; Dedi Setiadi (Institute of Computer Science (IOCS), 2021)
The Arrival and Departure sheet data storage system is a familiar thing in the LPPNI Public Corporation Halim Perdana Kusuma branch. But the problem of irregular storage and making reports that are not fast and accurate often become obstacles that must be experienced. Data storage Arrival and Departure sheet using a manual system results in frequent errors. In the development of the company to input and make reports Arrival and Departure sheet data still uses a manual system that requires accuracy and a very long process. Therefore the Arrival and Departure sheet data storage system will be able to solve the problem of inputting data and provide data reports quickly and accurately. The system development method in this study uses prototypes or prototypes which include planning, design, implementation and testing. The results of this research are to obtain application and testing on the system that will be developed with the results of black box testing.